Quantum capacitance as a reagentless molecular sensing element - Bueno, Paulo R. [UNESP]; Bedatty Fernandes, Flávio C. [UNESP]; Davis, Jason J. (Royal Society of Chemistry (RSC), 2017)
The application of nanoscale capacitance as a transduction of molecular recognition relevant to molecular diagnostics is demonstrated. The energy-related signal relates directly to the electron occupation of quantized states present in readily fabricated molecular junctions such as those presented by redox switchable self-assembled molecular monolayers, reduced graphene oxide or redox-active graphene composite films, assembled on standard metallic or micro-fabricated electrodes. Sensor design is thus based on the response of a confined and resolved electronic density of states to target binding and the associated change in interfacial chemical potential. Demonstrated herein with a number of clinically important markers, this represents a new potent and ultrasensitive molecular detection enabling energy transducer principle capable of quantifying, in a single step and reagentless manner, markers within biological fluid.